Treatment of cyclic vomiting syndrome with co-enzyme Q10 and amitriptyline, a retrospective study - Boles, Richard G; Lovett-Barr, Mary R; Preston, Amy; Li, B UK; Adams, Kathleen (BMC neurology, 2010)
Cyclic vomiting syndrome (CVS), which is defined by recurrent stereotypical episodes of nausea and vomiting, is a relatively-common disabling condition that is associated with migraine headache and mitochondrial dysfunction. Co-enzyme Q10 (Co-Q) is a nutritional supplement that has demonstrated efficacy in pediatric and adult migraine. It is increasingly used in CVS despite the complete lack of studies to demonstrate its value in treatment Using an Internet-based survey filled out by subjects with CVS or their parents, the efficacy, tolerability and subject satisfaction in CVS prophylaxis were queried. Subjects taking Co-Q (22 subjects) were compared against those taking amitriptyline (162 subjects), which is the general standard-of-care. Subjects/parents reported similar levels of efficacy for a variety of episode parameters (frequency, duration, number of emesis, nausea severity). There was a 50% reduction in at least one of those four parameters in 72% of subjects treated with amitriptyline and 68% of subjects treated Co-Q. However, while no side effects were reported on Co-Q, 50% of subjects on amitriptyline reported side effects (P = 5 x 10-7), resulting in 21% discontinuing treatment (P = 0.007). Subjects/parents considered the benefits to outweigh the risks of treatment in 47% of cases on amitriptyline and 77% of cases on Co-Q (P = 0.008). Our data suggest that the natural food supplement Co-Q is potentially efficacious and tolerable in the treatment of CVS, and should be considered as an option in CVS prophylaxis. Our data would likely be helpful in the design of a double-blind clinical trial.